Bacteriological quality of the ice cream consumed in Serres and Kilkis - ΠΑΝΑΠΩΤΙΔΟΥ-ΜΑΜΑΛΟΥΚΑ Β.; ΚΡΙΤΣΕΠΗ-ΚΩΝΣΤΑΝΤΙΝΟΥ Μ. (Journal of the Hellenic Veterinary Medical Society, 2019)
The microbiological quality of the icecream consumed in the district of Serres and Kilkis, was investigated during the summer of 1983 and 1984. For this purpose were examinated 107 samples of ice-cream of different kinds, that derived from various small of big factories manufacturing such products. The microbiological condition of the above samples was investigated by determining the total microflora counts, the coliforms, the E.coli, the staphylococci, the salmonellas and the yastsmolds. The examination of the samples pointed out that percentages 66,62% and 91,59% of these presented values of TPC and coliforms respectively distinctly lower than the allowed limits of the product. Even E.coli was present only in 6,54% of the samples. Salmonellae and staphilococci coagulase positive were isolated in none of the examined samples. The percentage of samples with high total plate-count and high number of coliforms compared with corresponding similar works taken up in Greece or other countries were in a same ratio. Therefore, the results show that the hygenic conditions throughout the production line of the ice-cream are not yet satisfactory.